Different Infective and Non-Infective Etiology of Exudative Pleural Fluid Effusion: Experience of 50 Cases in Bangladesh - Mohith, Muhammad Tanvir; Rahman, Mohammed Ziaur; Zannat, Tajin; Ansary, Abdullah Md Abu Ayub; Syed, Mahnaz; Kamal, Mostofa (Bangladesh Journal of Medical Microbiology, 2023)
Background: Several diseases are responsible for the causation of exudative pleural fluid effusion among patients. Objective: The purpose of the present study was to identify the etiologies of exudative pleural fluid effusion. Methodology: This cross-sectional study was carried out at medicine indoor department of Sylhet MAG Osmani Medical College Hospital, Sylhet over a period of six month from October 2009 to March 2010. Patients who were admitted with pleural effusion were selected as the study population. Pleural fluid was collected by a physician. The laboratory tests were performed in the Department of Laboratory medicine of the Hospital. The different etiologies were determined by the different diagnostic tests. Results: A total of 50 cases were selected consecutively in the study. Out of 50 patients, 28.0% was in the range of 41 to 50 years followed by 26.0% between 31 to 40 years. Tuberculosis was the most common cause of exudative pleural effusion and among 50 cases of effusion 30 were due to tuberculosis (60%). Malignancy was found as the 2nd common cause of exudative pleural effusion (24.0%). Pneumonia was found as the 3rd common cause of exudative pleural effusion (10.0%). Conclusion: In conclusion tuberculosis is the most common cause of exudative pleural effusion followed by malignancy. Bangladesh Journal of Medical Microbiology, January 2023;17(1):10-14 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />